Impact of carbendazim on cellular growth, defence system and plant growth promoting traits of Priestia megaterium ANCB-12 isolated from sugarcane rhizosphere - Sharma, Anjney; Song, Xiu-Peng; Singh, Rajesh Kumar; Vaishnav, Anukool; Gupta, Saurabh; Singh, Pratiksha; Guo, Dao-Jun; Verma, Krishan K.; Li, Yang-Rui (Frontiers in Microbiology, 2022)
Agrochemicals are consistently using in agricultural practices to protect the plants from pathogens and ensuring high crop production. However, their over consumption and irregular use cause adverse impacts on soil flora and non-target beneficial microorganisms, ultimately hazard to ecosystem. Taking this into account, present study was conducted to determine fungicide (carbendazim: CBZM) toxicity effects on the rhizobacteria survival, plant growth promoting trait and ROS scavenging antioxidant enzymes system. Thus, a multifarious plant growth promoting rhizobacteria (PGPR) isolate ANCB-12 was obtained from sugarcane rhizosphere through enrichment technique. Taxonomic position of the isolated rhizobacteria was conformed though 16S rRNA gene sequencing analysis as Priestia megaterium ANCB-12 (Accession No. ON878101). Results showed that increasing concentration of fungicide doses showed adverse toxic effects on rhizobacteria survival and cell growth which was decreased with increasing incubation time and concentration of fungicide. In addition, cell visualization under under confocal laser scanning microscope (CLSM) revealed about oxidative stress damaged in the form of more ROS generation and cell membrane permeability. Further, the increasing dose (1000-3000 µg/ml) of fungicide gradually decreased the plant growth promoting attributes activities of the rhizobacteria ANCB-12. Likewise, fungicide indorsed the reactive oxygen species (ROS) toxicity by significantly (p < 0.05) modulating the stress related antioxidant enzymatic biomarkers in P. megaterium ANCB-12. In conclusion, the finding of present study showed cellular toxic effects of higher dosage of carbendazim fungicide on plant beneficial rhizobacteria and suggest to design a recommended dose of fungicide to reduce their toxic/harmful effects